The Application Of The Principles Of Independence And Impartiality Of Judges In The Decision Of The Constitutional Court Number 90/PUUXXI/2023 Concerning The Age Limit Requirements For Nominating Presidents And Vice Presidents - Aryo Akbar; Efendi Ibnususilo; Faishal Taufiqurrahman (International Conference On Law And Social Sciences, 2024)
Recently, the public has been shocked by a controversial constitutional court decision, especially in the constitutional court decision number 90/PUU-XXI/2023. This is because in the decision, the chairman of the constitutional court participated in the trial and decided the case. Whereas in the decision there are interests of his nephew who participated in the political contestation of the general election of the President and Vice President. If there is a potential interest, the judge concerned should resign from the case related to the interests of his family. The purpose of this study is to determine the application of the principles of independence and impartiality of constitutional judges in decision number 90/PUUXXI/2023. This legal research uses a normative approach. One of them is to identify whether the law regulates a matter and how the rules are applied. The source of this research is secondary data sources consisting of primary legal materials, secondary legal materials and tertiary legal materials. Primary legal materials in this research are laws and regulations and the decision of the constitutional court number 90/PUU-XXI/2023. Secondary legal materials consist of literature, legal journals, and articles related to the principles of independence and impartiality. This research shows that the decision of the constitutional court number 90/PUU-XXI/2023 is ethically and morally flawed. This is because the judge did not apply the principles of independence and impartiality in the decision, so that the decision benefited one of the parties, where the party was the nephew of the chairman of the constitutional court. The author's recommendation is that a judge must be able to distinguish between his official attitude as a state official tasked with upholding justice, and the attitude of daily life as part of the family and society. If this is applied by judges, then the author believes that judges in carrying out their duties can apply the principles of independence and impartiality in deciding a case.